The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1186/1471-2334-8-154
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus intermedius causing infective endocarditis and abscesses: a report of three cases and review of the literature

Abstract: BackgroundStreptococcus intermedius is a member of the Streptococcus anginosus group. Clinical disease with S. intermedius is characterized by abscess formation and rarely endocarditis. Identification of Streptococcus intermedius is difficult, leading to the development of molecular methods to more accurately identify and characterize this organism.Case presentationOver a period of 6 months we encountered three cases of invasive Streptococcus intermedius infection presenting as hepatic abscesses, brain abscess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 33 publications
1
79
0
5
Order By: Relevance
“…7 Similar to the recommendations for the management of brain abscess, which may frequently be polymicrobial, initial antibiotic therapy with ceftriaxone and metronidazole was administered. In most reported cases, patients underwent surgical abscess drainage together with antibiotic treatment.…”
Section: Case Reportmentioning
confidence: 99%
“…7 Similar to the recommendations for the management of brain abscess, which may frequently be polymicrobial, initial antibiotic therapy with ceftriaxone and metronidazole was administered. In most reported cases, patients underwent surgical abscess drainage together with antibiotic treatment.…”
Section: Case Reportmentioning
confidence: 99%
“…It had been believed that deep-seated abscesses caused by AGS, including S. intermedius, are uncommon in healthy individuals without any identifiable risk factors such as immunocompromised states caused by diabetes, cirrhosis, and cancer (42)(43)(44). However, some reports have shown that S. intermedius can form deep-seated abscesses in the brain, lung, and spleen in healthy humans (45)(46)(47). It is important to analyze whether clinical isolates from such cases show high-ILY-producing phenotypes associated with lacR mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcus intermedius is a member of the Streptococcus anginosus group (SAG). Several retrospective reviews and case reports have mentioned S. intermedius as a significant pathogen among the SAG species in the development of brain abscess (2)(3)(4)(5). However, no studies have compared S. intermedius brain abscess with abscess caused by other SAG members or other bacteria.…”
Section: Introductionmentioning
confidence: 99%